Factors that Influence the Choice of Teaching EFL in Public Primary Schools in Colombia - Londoño, Pamela (Íkala, Revista de Lenguaje y Cultura, 2022)
In Colombian public elementary schools, there is a shortage of qualified English teachers. Hence, this study seeked to determine the factors associated with the choice of teaching as a profession, particularly those associated with the teaching of EFL at several public educational institutions in Santiago de Cali, Colombia. To gather information, we applied a biographic-narrative interview guide with four teachers. Findings show that choosing the teaching of foreign languages by these teachers was determined by sociological factors (such as family influences or contextual relationships, such as mother teachers or memorable teachers), psychological factors (related to love for teaching and for languages) and economic factors (associated with job stability). In conclusion, it is important to motivate teachers trained in English language teaching to choose primary school as a career, by considering their life and training experiences.